THE DYNAMICS OF TEMPERATURES CHANGING OF ROUND INGOT IN THE FIELD OF CUT AT ITS DRAWING ON THE MACHINE OF CONTINUOUS CASTING OF THE SMALL RADIUS SLUGS - A. N. Chichko; V. A. Matochkin; D. M. Kukuj; M. A. Murikov; A. V. Demin; O. I. Chichko (Литьë и металлургия, 2006)
The temperatures of the round ingot, produced in the machine of continuous casting with bending radius 5 meters, are calculated by means of numerical calculation. The dependence of the temperature in the field of ingot cutting on speed of the ingot moving and coefficients of the zones of primary and secondary cooling is determined.